# If f(x)=-2x^4+5 and g(x)=5x+1, what is f(-3)-g(3)?

*print*Print*list*Cite

### 2 Answers

`f(x)= -2x^4 +5` and `g(x)= 5x+1` so substitute for values of x

`therefore f(-3) - g(-3) = -2(-3)^4 + 5 - (5(-3) +1)`

= -2 (81) + 5 + 15 - 1 Take care with the symbols when you remove the brackets.

I see that I evaluated it using g(-3) my apologies. Therefore, g(3)should have been -(16) such that ....- (5 (3) +1)

-157 - 16= -173

So the answer as per "widowspeak" is **-173**

The above answer is correct except they forgot to add 5 to evaluate f(-3):

f(-3) = -2*(-3)^4 + 5 = -162 **+ 5** = -157

g(3) = 5*3 + 1= 16

f(-3) - g(3) = -157 - 16 = **-173**